Heat Shock Protein Inhibitors Success Stories - McAlpine, Shelli R.; Edkins, Adrienne Lesley; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Medicinal chemistry is both science and art. The science of medicinal chemistry offers mankind one of its best hopes for improving the quality of life. The art of medicinal chemistry continues to challenge its practitioners with the need for both intuition and experience to discover new drugs. Hence sharing the experience of drug research is uniquely beneficial to the field of medicinal chemistry. Drug research requires interdisciplinary team-work at the interface between chemistry, biology and medicine. Therefore, the topic-related series Topics in Medicinal Chemistry covers all relevant aspects of drug research, e.g. pathobiochemistry of diseases, identification and validation of (emerging) drug targets, structural biology, drugability of targets, drug design approaches, chemogenomics, synthetic chemistry including combinatorial methods, bioorganic chemistry, natural compounds, high-throughput screening, pharmacological in vitro and in vivo investigations, drug-receptor interactions on the molecular level, structure-activity relationships, drug absorption, distribution, metabolism, elimination, toxicology and pharmacogenomics. In general, special volumes are edited by well known guest editors. .
Targeting the C-Terminus of Hsp90 as a Cancer Therapy -- Hsp90 Co-chaperones as Drug Targets in Cancer: Current Perspectives -- Evaluating Dual Hsp90 and Hsp70 Inhibition as a Cancer Therapy -- The Effect of Structure and Mechanism of the Hsp70 Chaperone on the Ability to Identify Chemical Modulators and Therapeutics -- Allosteric Inhibitors of Hsp70: Drugging the Second Chaperone of Tumorigenesis -- Hsp40 Co-chaperones as Drug Targets: Towards the Development of Specific Inhibitors -- HSP47: The New Heat Shock Protein Therapeutic Target -- Heat Shock Protein 27: Structure, Function, Cellular Role and Inhibitors.
Keywords: Medicinal chemistry; Chemistry, Organic; Proteins .; Medicinal Chemistry; Organic Chemistry; Protein Biochemistry